THE ROLE OF SOCIAL MEDIA MARKETING ON PURCHASE INTENTION FOR THRIF CLOTHING MODERATED BY GENDER - Virdies Nur Cahya; Refius Pradipta Setyanto (CV. Radja Publika, 2025)
Research purposes:This study aims to analyze the influence of Social Media Marketing (SMM) on thrift clothing purchase intention with gender as a moderating variable. Research Methods: This study uses a quantitative approach with a survey method of 400 respondents who have purchased or are interested in thrift fashion products. Data analysis was conducted using multiple linear regression and moderated regression analysis (MRA) to test the interaction effect between SMM and gender. Originality/Novelty: The novelty of this study lies in the gender interaction approach in the digital marketing model for thrift products, which is still rarely studied in the context of Indonesian consumers. This study also contributes to the social media-based marketing literature with a focus on gender segmentation. Research Results: The results show that SMM has a positive and significant effect on thrift clothing purchase intention. Gender is proven to significantly moderate the relationship, with a stronger influence on the female consumer group. Findings from the multi-group analysis indicate that marketing strategies through social media are more effective in shaping women's purchase intention than men's. Implications: This study provides implications that digital marketing strategies need to be tailored to consumer demographic characteristics, particularly gender, to increase campaign effectiveness and purchase conversions in the thrift fashion industry.